2023
DOI: 10.31234/osf.io/7nfd4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental health literacy reduces the impact of internalized stigma on willingness to seek mental health services

Corey S. Mackenzie,
Melissa A. Krook,
Dallas James Murphy
et al.

Abstract: Objectives: Older adults (OA) are the age demographic least likely to seek help, and internalized stigma is an important reason why. We sought to further our understanding of which OA are particularly likely to be negatively impacted by internalized stigma, and why, by investigating mental health literacy (MHL) as a moderator within the internalized stigma model (ISM) of help seeking. Methods: We utilized conditional-process analysis of cross-sectional, secondary data from 350 distressed OA. Participants compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…This adds to the list of variables that are emerging as moderators of the internalized stigma model in older adults. This list includes PC, mental health literacy (Krook et al, 2023), and experiential avoidance (Murphy & Mackenzie, 2023). This work is beginning to provide (a) a nuanced picture of which older adults are least likely to seek help for mental health services despite a potential need and (b) mechanisms of change to target when developing interventions to help those at-risk older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This adds to the list of variables that are emerging as moderators of the internalized stigma model in older adults. This list includes PC, mental health literacy (Krook et al, 2023), and experiential avoidance (Murphy & Mackenzie, 2023). This work is beginning to provide (a) a nuanced picture of which older adults are least likely to seek help for mental health services despite a potential need and (b) mechanisms of change to target when developing interventions to help those at-risk older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Despite structural barriers to seeking help that are beyond the purview of individuals to change, this study points to an individual barrier that may be modified. Our work adds PC as moderator, alongside experiential avoidance (Murphy & Mackenzie, 2023) and mental health literacy (Krook et al, 2023), all of which may serve as malleable targets of intervention. Together, the foundations for an intervention rooted in established theory with evidence-backed mechanisms of change are beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this work can be extended to clinical samples to understand the influence of personality on the help seeking of more at-risk populations. Second, research has found other established predictors, such as experiential avoidance (Brenner et al, 2020; Murphy & Mackenzie, 2023), perceived control (Murphy et al, 2024), and mental health literacy (Mackenzie et al, 2023) to moderate the internalized stigma model, and research might explore personality as a moderator. Third, research has explored longitudinal changes in personality (e.g., Roberts et al, 2006; Srivastava et al, 2003); similar work that includes mental health service use variables would help clarify the interactions among these variables over time.…”
Section: Discussionmentioning
confidence: 99%